Implementasi Metode Local Weighting Pattern pada Prototype Ciri Frame Dinamis - Sumadi, Muhammad Taufiq; Putra, Arief Bramanto Wicaksono; Vidyanesa, Bunga Shafa (Jurnal Informatika: Jurnal Pengembangan IT, 2022)
In this age of technology, digital image and video processing is a fairly desirable field of science. Digital image and video can be used in various fields, one of which is industry, this has led to the development of digital images and video in the rapidly developing world of technology. Along with the development of digital image technology, object recognition in the image requires an increase in the algorithm in this case is the extraction of image features which of course also develops in the application of video. Video is a collection of images that are recorded or acquired during a certain unit of time. In this study, feature extraction was carried out using Local Weighting Pattern. As the object of research used video data. The results of the analysis are based on feature extraction experiments that have been carried out in this research, if the difference between frames is more than 0.045, then there is a change in the frames, if it is less than equal to 0.045 then vice versa